2021
DOI: 10.1093/eurpub/ckab076
|View full text |Cite
|
Sign up to set email alerts
|

Household food spending, parental and childhood’s diet quality, in financial crisis: a cross-sectional study in Greece

Abstract: Background Over the past decade, the financial crisis has affected harshly the household income of Greek people. This study aimed to investigate whether the effect of the financial crisis on food spending has affected the dietary habits in the family environment. Methods Under a cross-sectional study conducted during 2014–2016, 1145 children and their parents completed questionnaires examining socio-economic and dietary chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similar findings were demonstrated in Portugal, where a significant decrease in consumption of fish, fruit and vegetables was recorded from 2005/2006 to 2014 [29]. A cross-sectional study from Greece showed that parents who reported that the financial crisis affected their food spending also reported lower consumption of fruits, carbohydrate foods, and legumes, and increased intake of nutrient-poor/energy-dense foods, while their children had reduced weekly consumption of vegetables and increased weekly consumption of nutrient-poor/energy-dense foods [89]. These and other recent evidence show a possible involvement of the economic crisis, and material resources as strong determinants of adherence to the MD in the period after the recession started [90], given that a direct positive association between the cost of the diet and adherence to the MD has been established [36].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were demonstrated in Portugal, where a significant decrease in consumption of fish, fruit and vegetables was recorded from 2005/2006 to 2014 [29]. A cross-sectional study from Greece showed that parents who reported that the financial crisis affected their food spending also reported lower consumption of fruits, carbohydrate foods, and legumes, and increased intake of nutrient-poor/energy-dense foods, while their children had reduced weekly consumption of vegetables and increased weekly consumption of nutrient-poor/energy-dense foods [89]. These and other recent evidence show a possible involvement of the economic crisis, and material resources as strong determinants of adherence to the MD in the period after the recession started [90], given that a direct positive association between the cost of the diet and adherence to the MD has been established [36].…”
Section: Discussionmentioning
confidence: 99%
“…As previous research reports, a large part of the Greek population and particularly children, have moved further away from the MD in terms of fruit, vegetable, and legumes consumption frequency; however, the core characteristics of MD remained resilient and in recent years there is even more interest in the traditional and regional dietary habits [21][22][23]. Additionally, the consumption of fresh and dried herbs, including MAPs, as part of the dietary pattern in Greece, has also been identified as a beneficial contributor toward healthy and sustainable nutrition [24].…”
Section: Introductionmentioning
confidence: 90%
“…Such shift was probably associated to the inflation of prices which was evident in the country during the time of financial austerity. Research by Barda and Sardianou (2010), indicated that Greek consumers were limited in the consumption of fruits due to increasing food prices and decrease in monthly wages, while Kosti et al (2021) showed that a large amount of the Greek population (98%) compared to other Europeans (80%), considered prices as a significant factor for purchasing healthy food. Indeed, during the economic crisis in Greece, fruit and vegetable costs have increased by 12.5% between 2006 and 2011 (Filippidis et al, 2014).…”
Section: Healthy Diet Choices During Austeritymentioning
confidence: 99%